Factors for arboviral seropositivity in children in Teso South Sub County, Kenya - Mary Inziani; Jane Mawia Kilonzo; Marthaclaire Kerubo; Sylvia Mango; Mary Kavurani; Allan Ndirangu; Elizabeth Njeri; Diuniceous Oigara Ogenche; Sylvester Ogolla Ayoro; Shingo Inoue; Kouichi Morita; Matilu Mwau (PLoS ONE, 2025)
Background Arboviruses like Yellow Fever Virus (YFV), Dengue Virus (DENV), Chikungunya Virus (CHIKV), and West Nile Virus (WNV) frequently cause outbreaks in sub-Saharan Africa. Identifying risk factors in children can improve diagnosis, treatment, and prevention strategies. This study identified factors associated with seropositivity to YFV, DENV, CHIKV and WNV among children in Teso South Sub-County, Western Kenya. Methods This survey involved 656 children aged 1–12 years, enrolled at two health facilities. Socio-demographic, environmental, behavioral, and medical information was collected via a questionnaire. Serological screening for antibodies to YFV, DENV, CHIKV, and WNV was performed using Indirect Enzyme-Linked Immunosorbent Assays. The collected data was summarized using descriptive statistics. Factors associated with seroprevalence were examined using multinomial logistic regression. Results Overall, 27.7% of children were seropositive for at least one arbovirus: 15.7% for DENV, 9.6% for WNV, 5.6% for CHIKV, and 4.4% for YFV. Factors associated with any arbovirus were: female gender, age 6–9 and 9–12 years, non-parent primary caregiver, and use of unknown bed nets brand (p < 0.05). YFV seropositivity was not associated with any of the risk factors, while DENV was associated with female gender and age 6–9 years (p < 0.05). CHIKV was associated with use of insect repellents and not using any mosquito bed nets. WNV seropositivity was significantly higher in all children aged above 3 years, those who lived in town/urban areas, use of olyset, supanet and unknown bed nets and in those who lived in houses roofed with tiles and iron sheets (p < 0.05). Conclusion Arbovirus exposure among children is influenced by age, female gender, non-parental primary care giver, failure to use mosquito bed nets, type of bed net, use of insect repellents, and house roofing material. Interventions targeting housing improvements, education on bed net and mosquito repellent use, and environmental mosquito control can reduce infection risks in endemic areas.